Epidemiological And Clinical Outcomes Of Tuberculosis With Its Co-Morbidities In General Population And In Prisons In Malaysia - Amer Hayat Khan, (2011)
The threat of tuberculosis (TB) seemed to have become increasingly looming with the fatal combination of co-morbid conditions like human immunodeficiency virus (HIV)-acquired immune deficiency syndrome (AIDS), diabetes mellitus (DM) and hepatitis. Ancaman penyakit tuberkulosis (TB) menunjukkan peningkatan yang ketara dengan ancaman kematian kepada kombinasi TB dengan status komobiditi seperti Virus Kurang Daya Tahan Penyakit (HIV)-Sindrom Daya Kurang Tahan Penyakit (AIDS), diabetes mellitus (DM) dan penyakit hepatitis.